MEKANISME PERGANTIAN ANTAR WAKTU ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH - Poiran; Joko Sunaryo; Hamirul (Bajang Institute, 2021)
Problems in political parties are very numerous, but one of them is the change between DPRD members in terms of the composition of political parties using the descriptive method of qualitative approach, using data collection techniques with interviews and informants used in this study as many as 11 people with results obtained between the time of DPRD members in terms of the composition of moving political parties in the DPD Golkar Party DPD, namely: (1). PAW proposal by party leaders to DPRD leaders. (2). Approval at the DPRD plenary meeting. (3). Verification and clarification by KPU. (4). Propose PAW to the Governor. The obstacles faced in the change between the time the DPRD members who moved political parties in the DPD Golkar Party DPD were: (1). Incomplete PAW filing file. (2). Time of inspection by relevant officials. Efforts are being made to overcome barriers to facilitate the replacement of time between DPRD members who move political parties to the Bungo Regency Golkar Party DPD, namely: (1). Complete the PAW proposal file. (2). Following-up on PAW files processed by the Governor.